A Social Norms and Identity Approach to Increasing Fruit and Vegetable Intake of Undergraduate Students in the United Kingdom - Fischera, Wanda; van Beusekom, Mara; Higgs, Suzanne; Cecil, Joanne E. (Frontiers in Psychology, 2022)
This study investigated the influence of descriptive norm messages that either communicated that university students eat a sufficient amount of fruit and vegetable (F&V) or that they do not, on F&V consumption, and whether or not any effects are moderated by student identification. An online 2 (Norm: ‘Sufficient’/‘Insufficient’) x 2 (Identification: ‘Low’/‘High’) experimental design was employed. Infographics containing ‘sufficient’/‘insufficient’ F&V intake descriptive norms were presented. An identification manipulation was employed to create ‘high’/‘low’ student identifiers. F&V intake intentions were assessed after the manipulations; self-reported F&V intake was reported at 2 days post-intervention. UK undergraduate students (N=180) reported intake intentions, of which 112 (62%) completed the behavioral follow-up. Participants were predominantly white female students from Scottish universities, mean age 20.4 (±1.6) years. Baseline mean F&V consumption was high (4.5±2.8). There were no significant main effects of Norm or Identification manipulations on F&V intentions and intake. Significant norm×identification interactions were revealed for fruit intake intentions and vegetable intake at follow-up, indicating half portion differences (~40g) between groups. Ironic effects were observed for ‘high’ identifiers, who neither intended to, nor acted in accordance with group norms; ‘low’ student identifiers intended to and followed group norms, whereby the ‘sufficient’/‘low’ group intended to consume significantly more fruit portions, and consumed more vegetables than the ‘insufficient’/‘low’ group. Given the half-portion differences between groups resulting from the norm×identification interactions, future research on a larger sample of young adults with low F&V intake is warranted to further explore the conditions under which moderating effects of identification are observed and the underlying mechanisms.